1993
DOI: 10.1139/v93-009
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of epoxides via Sharpless epoxidation of alkenylsilanols

Abstract: Enantioselective synthesis of simple epoxides can be achieved by Sharpless epoxidation of alkenylsilanols followed by protodesilylation of the chiral epoxysilanols. The approach has been applied to the synthesis of frontalin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 10 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In practice the idea does work. The silanol 1884 gave the epoxide 1885 in moderately high enantiomeric excess, and the reaction was used, with subsequent protodesilylation, for a synthesis of frontalin 1887 (Scheme ) . The same type of reaction was used in the kinetic resolution of a chiral silyl compound (Scheme ).…”
Section: F Silicon-bridged Epoxidationmentioning
confidence: 99%
“…In practice the idea does work. The silanol 1884 gave the epoxide 1885 in moderately high enantiomeric excess, and the reaction was used, with subsequent protodesilylation, for a synthesis of frontalin 1887 (Scheme ) . The same type of reaction was used in the kinetic resolution of a chiral silyl compound (Scheme ).…”
Section: F Silicon-bridged Epoxidationmentioning
confidence: 99%
“…One representative example is the application of enantioselective Sharpless epoxidation reactions to alkenylsilanols instead of allylic alcohols that has been investigated since the first report by Chan . They found that a variety of alkenylsilanols 50 were applicable to Sharpless-type epoxidation to afford the corresponding epoxides substituted with hydroxysilyl groups 51 (Scheme ).…”
Section: Silanols As Temporary Ligands To Control Regioselectivity Of...mentioning
confidence: 99%